Analisis Kinerja Pengolahan Biogas di PT. Mitra Puding Mas Kecamatan Putri Hijau Kabupaten Bengkulu Utara Provinsi Bengkulu - Elyswandy Simanjuntak Wandy; Hesti Nur’aini; Andwini Prasetya (Universitas Merdeka Madiun, 2024)
PT. Mitra Puding Mas is one of the oil palm fruit processing factories in Bengkulu Province. POME palm oil mill effluent is the largest waste generated from the palm oil production process. The largest components contained in biogas are CH4 (50 % – 75 %) and CO2 (24% - 45 %) as well as several percent, nitrogen and hydrogen sulfide. The purpose of this study was to determine the composition of biogas CH4, O2, CO2 and H2S as well as the factors that affect the performance of biogas processing production at PT Mitra Puding Mas. Processing performance was obtained by using secondary data collection methods and literature study, while the factors influencing performance were obtained through interviews and observations. The results of the analysis of the performance of the biogas processing process, CH4 (53.6%), CO2 (36.18%), O2 (1.14%) and H2S (1.92 ppm) were categorized according to the standard composition of biogas liquid waste from palm oil. Factors that affect the performance of biogas processing are categorized very well, in the human aspect, namely the employees are skilled and expert in biogas management, in the raw material aspect, namely the use of palm oil or POME liquid waste as biogas raw material, in the method aspect, namely work instructions according to the SOP before and during the production process; on the machine aspect that is always checked regularly or periodically to avoid damage.